THE GRADUATES OF DORPAT PROFESSORIAL INSTITUTE -PROFESSORS OF A NEW FORMATION - Nadezhda V. Karnaukh (Moscow Polytechnic University, 2016)
The present article contains the author's research results on the peculiarities of Professorial Institute graduates' academic activity. The Professorial Institute was founded in the first quarter of 19th century at Dorpat imperial university. The training system for professors of a new formation in this Institute is examined by the author as academic school. Due to the analysis of professional activities of the Professorial institute graduates, the author comes to a conclusion that this activity was impelled by the ideas about the role and image of a Russian university professor. These ideas were formed in the atmosphere of Professorial institute academic school. There were common essential features that characterize the graduates of the Professorial institute such as encyclopedic scientific knowledge, lecture skills, effective methods of teaching, methods of fostering students for investigation and teaching activities. Appealing to the history of professors training at Russian universities in the 19th century enables us to find reasonable solutions of the topical problems facing higher education system in the period of current reformation.